2014
DOI: 10.1080/02640414.2014.918273
|View full text |Cite
|
Sign up to set email alerts
|

Return to play management after concussion in football: recommendations for team physicians

Abstract: A concussion is a rare but potentially serious injury of football players. Thus, an immediate and valid diagnosis, estimate of severity and therapeutic management is required. To summarise the published information on management of concussion with respect to a safe return to play (RTP), a literature search was conducted. Current guidelines on concussion in sports and significant studies on concussion in football were analysed. After concussion, management and RTP decision should remain in the area of clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 73 publications
0
13
2
Order By: Relevance
“…The frequency and incidence seem to be in the lower range of previously reported data for adolescent and adult players. 9 Recent data from a retrospective analysis of head injuries in U.S. high schools showed higher incidences as compared to our data. 2 These authors observed 2.8 concussions per 10 000 athlete exposures in boys.…”
Section: Key Resultscontrasting
confidence: 46%
See 2 more Smart Citations
“…The frequency and incidence seem to be in the lower range of previously reported data for adolescent and adult players. 9 Recent data from a retrospective analysis of head injuries in U.S. high schools showed higher incidences as compared to our data. 2 These authors observed 2.8 concussions per 10 000 athlete exposures in boys.…”
Section: Key Resultscontrasting
confidence: 46%
“…7,8 As a consequence of the above-mentioned potentially serious sequelae, evidencebased consensus guidelines on the management of concussions and return to training, to competition, to work or to school have recently been developed. [9][10][11][12][13] Children and adolescents represent the largest portion of active football players worldwide. 4,14 Several functional, structural as well as cognitive characteristics differ between the maturing athlete and adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore essential to diagnose how serious the concussion is and to avoid later consequences, so the player should only return to the match if this is safe. In cases of cerebral contusion the player should never play again on the same day, even if he has no symptoms and the clinical examination is normal 26 . The knee joint suffers the most severe injuries in soccer, many of which require surgical treatment.…”
Section: O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…This has resulted in a general lack of measures that are aimed directly at preventing the occurrence of situations that lead to concussion. Much of the recent literature around concussion has limited its focus to the adoption of management guidelines post-concussion or to the effectiveness of headgear, rather than primary prevention (Hollis et al 2012; Feddermann-Demont et al 2014). Although important, such approaches correspond only to the later-stage levels of countermeasure strategies, outlined by Haddon (Haddon 1973).…”
Section: Discussionmentioning
confidence: 99%